In vitro activity of the novel oral antimicrobial SMT-571, with a new mechanism of action, against MDR and XDR Neisseria gonorrhoeae: future treatment option for gonorrhoea?. (18th February 2019) - Jacobsson, Susanne; Mason, Clive; Khan, Nawaz; Meo, Paul; Unemo, Magnus
Abstract: Background: Lack of effective treatment of gonorrhoea due to increasing antimicrobial resistance in Neisseria gonorrhoeae is a serious threat to the management and control of the infection. Novel antimicrobials are required to prevent the infection becoming untreatable. Objectives: Herein, we investigated the in vitro activity of a novel small-molecule antimicrobial with a new mechanism of action, SMT-571, against a large collection of clinical N. gonorrhoeae isolates ( n =  228) and international gonococcal reference strains ( n =  34), including numerous MDR and XDR gonococcal isolates. Methods: MICs of SMT-571 were determined by agar dilution and MICs of ceftriaxone, cefixime, azithromycin, ciprofloxacin, ampicillin, spectinomycin and tetracycline were determined by Etest. Results: SMT-571 showed potent in vitro activity against all the tested N. gonorrhoeae isolates ( n =  262). The MICs ranged from 0.064 to 0.125 mg/L and the MIC50, MIC90 and modal MIC were all 0.125 mg/L. No cross-resistance or correlation between the MICs of SMT-571 and comparator agents was seen. Conclusions: SMT-571 demonstrated potent in vitro activity against all tested gonococcal isolates and no cross-resistance to previously and currently used antimicrobials was seen. With its promising supplementary in vitro and in vivo preclinical data, including high levels of oral bioavailability, SMT-571 could be an effective option for the oral treatment of gonorrhoea. Randomized controlled clinical trials for gonorrhoea that examine the treatment efficacy, pharmacokinetics/pharmacodynamics, toxicity and safety of SMT-571, and include urogenital and extragenital (rectal and pharyngeal) samples, are crucial.